Understanding the learning needs to enhance clinical competence of new professional nurses in public hospitals of South Africa: A qualitative study - Kholofelo L. Matlhaba; Naomi L. Nkoane (Belitung Nursing Journal, 2022)
Background: A competent nursing workforce plays an important role, as it will ensure effective management of the healthcare system by providing quality nursing care. However, from the literature, it is evident that the learning needs of new professional nurses are not well explored and documented. Objective: The objective of this paper was to report identified learning needs of new professional nurses to enhance their clinical competence to ensure that they are able to provide excellent quality nursing care to patients with confidence. Methods: A qualitative study design was used to understand the perceptions of operational managers regarding the learning needs of new professional nurses to enhance their clinical competence. The study was conducted at seven public hospitals in the three districts of the North West Province, South Africa, between September and November 2021. Data were analyzed thematic. Results: Four themes emerged from data analysis: 1) Ethos and professional practice, 2) Management and leadership skills, 3) Assessment and observation skills, and 4) Documentation and record keeping. Conclusion: This study provides valuable information regarding the learning needs of new professional nurses. Understanding these learning needs can provide insight into how to better transition student nurses to registered nurses so that they are able to adequately and safely take care of a diverse patient population and work successfully as new nurses.